2019
DOI: 10.3389/fnut.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Framing on Acceptance of Cultured Meat

Abstract: Cultured meat can be produced from growing animal cells in-vitro rather than as part of a living animal. This technology has the potential to address several of the major ethical, environmental, and public health concerns associated with conventional meat production. However, research has highlighted some consumer uncertainty regarding the concept. Although several studies have examined the media coverage of this new food technology, research linking different frames to differences in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
117
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(147 citation statements)
references
References 59 publications
10
117
1
1
Order By: Relevance
“…Additionally, agribusinesses, commodity groups, and researchers should develop strategic talking points and social media strategies to engage in online conversations about cultured meat. These themes show some similarities to themes and perceptions identified in previous studies (Bryant & Barnett, 2018;Bryant & Dillard, 2019;Goodwin & Shoulders, 2013;Laestadius & Caldwell, 2015;Wilks & Phillips, 2017). However, researchers in the different studies elected different names for similar themes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Additionally, agribusinesses, commodity groups, and researchers should develop strategic talking points and social media strategies to engage in online conversations about cultured meat. These themes show some similarities to themes and perceptions identified in previous studies (Bryant & Barnett, 2018;Bryant & Dillard, 2019;Goodwin & Shoulders, 2013;Laestadius & Caldwell, 2015;Wilks & Phillips, 2017). However, researchers in the different studies elected different names for similar themes.…”
Section: Discussionsupporting
confidence: 69%
“…Respondents identified taste, price, and unnaturalness as barriers to consumption (Bryant & Barnett, 2018;Wilks & Phillips, 2017). Finally, a recent experimental study exposed U.S. consumers to different communication frames on cultured meat (Bryant & Dillard, 2019). Consumers were found to have significantly more negative attitudes when a "high tech" frame was used to discussed cultured meat (Bryant & Dillard, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Associating meat with lab technology appears to be off-putting to many consumers. Bryant and Dillard (2019) investigated the acceptance of lab-grown meat under different frames, highlighting either: the societal benefits of its consumption ("reducing harm to the environment and helping animals"), its technological novelty ("high tech"), or that cultured and conventional meat are the "same". The authors found that the high-tech framing group reported the least positive attitudes toward lab-grown meat and its consumption.…”
Section: Impact Of Framing On Food Perceptionmentioning
confidence: 99%
“…There have already been other studies investigating the acceptance of cultured meat in places, such as USA (14,15) and the Netherlands (16); comparisons have been made between consumers in USA, China and India (17); the USA and the UK (18); and China, Ethiopia and the Netherlands (19). Systematic literature reviews highlight the demographic and geographic variations between consumers (20,21) as well as the need for further research.…”
Section: Cultured Meatmentioning
confidence: 99%